2021
DOI: 10.3892/ol.2021.12497
|View full text |Cite
|
Sign up to set email alerts
|

Lycorine hydrochloride induces reactive oxygen species‑mediated apoptosis via the mitochondrial apoptotic pathway and the JNK signaling pathway in the oral squamous cell carcinoma HSC‑3 cell line

Abstract: Poor drug efficacy is a prominent cause of oral squamous cell carcinoma (OSCC) treatment failure. Although increased efforts in developing OSCC therapeutic strategies have been achieved in recent decades, the 5-year survival rate of patients with OSCC remains poor and effective drugs to treat OSCC are lacking. The aim of the present study was to investigate the apoptotic effect caused by lycorine hydrochloride (LH) and to identify its mechanism in the OSCC HSC-3 cell line. The findings demonstrated that LH eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…TCM have been shown to possess distinct advantages over commonly used chemotherapy medicine, such as low cost, high stability and minimal side effects [ 7 , 8 ]. Lycroine (Ly), a natural active alkaloid, exhibits a wide range of pharmacological effects [ 9 11 ], including an excellent antitumor effect on various cancers [ 4 , 12 14 ]. Our previous work [ 14 ] and other two studies [ 4 , 15 ] have already confirmed that Ly possess remarkable therapeutic potential for OS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TCM have been shown to possess distinct advantages over commonly used chemotherapy medicine, such as low cost, high stability and minimal side effects [ 7 , 8 ]. Lycroine (Ly), a natural active alkaloid, exhibits a wide range of pharmacological effects [ 9 11 ], including an excellent antitumor effect on various cancers [ 4 , 12 14 ]. Our previous work [ 14 ] and other two studies [ 4 , 15 ] have already confirmed that Ly possess remarkable therapeutic potential for OS.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work [ 14 ] and other two studies [ 4 , 15 ] have already confirmed that Ly possess remarkable therapeutic potential for OS. Studies suggested that antitumor effects of Ly might be associated with mitochondrial dysfunction in various types of cancer [ 12 , 15 , 16 ], including OS [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work [12] and other two studies [4,13] have already con rmed that Ly possess remarkable therapeutic potential for OS. Studies suggested that antitumor effects of Ly are associated with mitochondrial dysfunction in various types of cancer [10,13,14], including OS [13].…”
Section: Introductionmentioning
confidence: 99%
“…TCM have been shown to possess advantages over commonly used chemotherapy medicine, such as low cost, high stability and minimal side effects [5,6]. Lycroine (Ly), a natural active alkaloid, possesses a wide range of pharmacological effects [7][8][9], including an excellent antitumor effect on various cancers [4,[10][11][12] . Our previous work [12] and other two studies [4,13] have already con rmed that Ly possess remarkable therapeutic potential for OS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation